Wettability of Low Weight Borides by Commercial Aluminum Alloys − A Basis for Metal Matrix Composite Fabrication1 . Issue 11 (26th August 2016) - Ploetz, Steven; Nowak, Rafal; Lohmueller, Andreas; Sobczak, Natalia; Singer, Robert F.
Abstract : Boron compounds are promising candidates for reinforcement of metals because of their high strength and stiffness at low specific weight. For composite fabrication the wetting behavior is important. Isothermal wetting of B4 C, AlB2, CaB6, MgB2, and TiB2 by liquid pure aluminum (99.5%) and the alloy AlSi10MgMn is studied at 700 °C for 15 min in vacuum using the dispensed drop method. No wetting occurs during testing for all substrates. The contact angles remain constant for CaB6, MgB2, and TiB2, while for AlB2 and B4 C substrates a continuous decrease in contact angle value with time is observed. Abstract : Isothermal wetting kinetics of liquid aluminum on solid boron compounds (AlB2, B4 C, CaB6, MgB2, TiB2 ) are investigated at typical aluminum casting temperatures and are quantified in terms of the contact angle. No wetting (contact angles <90°) occurs at testing conditions, but for B4 C and AlB2 the contact angle decreases over time.